Study the biological activity of some antibiotics and theircomplexes, with some metals - A. Al-Tai, Heyam; T. Hameed, Rawaa; O. Al-Allaf, Yasser (Tikrit Journal of Pharmaceutical Sciences, 2023)
The research is concemed with studying of activity of some antibiotics (Tetracycline, Gentamycine and streptomycine) and their complexes with some metal (Ca, Mg ,Fe) were been studied by electric conductivity, ultraviolet spectroscopy (UV) to compare the biological effects of these complexes with the physiochemical methods for determination of this complexes such as association constant Ka, equivalente conductance (A) at infinit dilution and the distance between ions in solution R at the best fit values of standard deviation (c'A) which are caloulated for each antibiotic and their complexes with the absorbance of these complexes in neutral medium at room temperature.